The Influence Of Leadership Style On Employee Performance At South Bogor District Office - Aldiyansyah, Muhammad; Casilam, Casilam (Pascasarjana Universitas Pasundan, 2024)
This study aims to determine how much influence between leadership style on employee performance at the South Bogor District Office. The type of research used is field research with quantitative methods. The population and sample in this study were employees of the South Bogor District Office. totaling 40 employees, with the sample method, namely the total sampling method by conducting a classical assumption test, determination coefficient test, simple linear regression equation test and t-test. The data collection technique was by distributing questionnaires to 40 respondents at the South Bogor District Office using a Likert scale and the data analysis technique used in this study was using the SPSS program version 22.00 for windows. The results obtained from this study based on the t-test conducted were 10.164> is 2.018 so it can be concluded that there is a significant influence between leadership style on employee performance at the South Bogor District Office.